2018
DOI: 10.21037/jgo.2017.06.12
|View full text |Cite
|
Sign up to set email alerts
|

Current status of immunotherapy and immune biomarkers in gastro-esophageal cancers

Abstract: Gastroesophageal (GE) cancers continue to be a significant cause of mortality globally. Despite therapeutic advances in oncology, the prognosis of advanced GE cancer remains exceedingly poor. Immunotherapy has caused a major paradigm shift in the field of oncology. Not all patients benefit from these agents and several studies are trying to identify predictive and prognostic biomarkers to better inform and guide treatment decisions. The potential role of immunotherapy in GE cancers is emerging. These cancer ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Various studies have indicated that changes in immune cellular components in peripheral venous blood could reflect the inflammation status of the tumour, which is valuable in predicting survival prognosis [12,13]. It is increasingly speculated that the inflammation and tumour are correlated, resulting in the establishment of novel biomarkers of cancer for the evaluation of the prognostic significance [14]. Reportedly, neutrophils reflect the status of the systematic inflammation and accelerate the remodelling of the extracellular matrix [15].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have indicated that changes in immune cellular components in peripheral venous blood could reflect the inflammation status of the tumour, which is valuable in predicting survival prognosis [12,13]. It is increasingly speculated that the inflammation and tumour are correlated, resulting in the establishment of novel biomarkers of cancer for the evaluation of the prognostic significance [14]. Reportedly, neutrophils reflect the status of the systematic inflammation and accelerate the remodelling of the extracellular matrix [15].…”
Section: Discussionmentioning
confidence: 99%
“…Tremelimumab, a humanized monoclonal antibody against CTLA4, was tested in metastatic melanoma as the second‐line setting. Although its efficacy is not ideal, its combination with PD‐1 inhibitors has indeed attracted attention . Ipilimumab,another monoclonal antibody, activates the immune system by targeting CTLA4.…”
Section: Several Clinical Trials Of Immunotherapy For Esophageal Cancermentioning
confidence: 99%
“…57 It has been reported that the expression of PD-L1 in tumor cells and tumor-infiltrating immune cells is significantly associated with good overall survival, however, some reports are just the opposite. 6,8,37,42,58,59 The better the tumor differentiation, the negative lymph node metastasis and the early stage tumors have a higher expression rate of PD-L1. But some reports are just the opposite.…”
Section: Patients Who Can Benefit From Immunotherapy?mentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxic chemotherapy provides only modest benefit, with median overall survival (OS) reported in the range of 9-11 months. Until recently, only two targeted treatment options were available: firstline setting: Trastuzumab (for Her-2 positive GC) and second-line setting: Ramucirumab [4,5].…”
Section: Introductionmentioning
confidence: 99%